1969
DOI: 10.1111/j.1476-5381.1969.tb08503.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cyclic 3′,5′‐AMP and other adenine nucleotides on the melanophores of the lizard (Anolis carolinensis)

Abstract: . Cyclic 3′,5′‐AMP has been reported to darken skins of the frog, Rana pipiens. This suggests that cyclic 3′,5′‐AMP may mediate the action of MSH on amphibian chromatophores. Since MSH also darkens skins of the lizard, Anolis carolinensis, we investigated the effects of cyclic 3′,5′‐AMP and other nucleotides on Anolis melanophores to determine whether cyclic 3′,5′‐AMP may be the intracellular mediator of hormone action on melanophores of another vertebrate class. . Cyclic 3′,5′‐AMP, itself, causes a rapid mela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1970
1970
1982
1982

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Melanocyte-stimulating hormone causes darkening of the frog skin. Theophylline (ABE et aI., 1969), cAMP and dBcAMP (NOVALES and DAVIS, 1967;HADLEY and GOLDMAN, 1969) mimic this effect. Stimulation of p-receptors by isopropylnoradrenaline or by salbutamol also causes darkening of the skin (GOLDMAN and HADLEY, 1969a and b).…”
Section: E) Frog Skinmentioning
confidence: 77%
“…Melanocyte-stimulating hormone causes darkening of the frog skin. Theophylline (ABE et aI., 1969), cAMP and dBcAMP (NOVALES and DAVIS, 1967;HADLEY and GOLDMAN, 1969) mimic this effect. Stimulation of p-receptors by isopropylnoradrenaline or by salbutamol also causes darkening of the skin (GOLDMAN and HADLEY, 1969a and b).…”
Section: E) Frog Skinmentioning
confidence: 77%
“…Kim, Shulman & Levine (1968) reported that Db-cAMP was less effective than cAMP in causing relaxation of the isolated rabbit ileum, and Ryan & Heidrick (1968) showed that Db-cAMP was less effective as an inhibitor of cell growth in tissue culture. There are, furthermore, several reports of Db-cAMP producing responses different from those of the parent compound on various preparations including skeletal muscle (Chambaut, Ebou6-Bonis, Hanoune & Clauser, 1969) melanophores (Hadley & Goldman, 1969), isolated fat cells (Solomon, Brush & Kitabehi, 1970), HeLa cells (Hilz & Tarnowski, 1970) and intestinal smooth muscle (Bowman & Hall, 1070). In the experiments reported here the actions of cAMP with Db-cAMP when injected into the hypothalamic region of the cat brain are compared.…”
Section: Discussionmentioning
confidence: 99%
“…Effects on glucose uptake in mammalian skeletal muscle (166), on glucose oxidation in fat cells (149 ), and on melanocyte dispersion in lizard skin (167 ) can be cited as examples here. Effects on glucose uptake in mammalian skeletal muscle (166), on glucose oxidation in fat cells (149 ), and on melanocyte dispersion in lizard skin (167 ) can be cited as examples here.…”
Section: Additional Considerationsmentioning
confidence: 99%